METODE PELAKSANAAN PEKERJAAN TANGGUL BIOGAS STUDI KASUS : PROJECT OF BIOGAS (COVERED LAGOON) TO FLARING MSL CARGILL - Wahyu Araska; Rangga Fernando; Ilham Ahmad Syauki (Jurnal Ilmiah Poli Rekayasa, 2025)
Soft soil work is a major challenge in berm construction due to the physical and mechanical characteristics of the soil. Soft soil generally has high moisture content, large porosity, and weak grain structure, which leads to very low soil bearing capacity. These conditions result in the soil being unable to support the construction load optimally, thus increasing the risk of settlement and lateral deformation. These factors create challenges in the planning and execution of earthworks, as specialized methods are required to improve the soil's stability and strength to ensure the berm functions safely and effectively. The proper working methods for handling soft soil can maintain the stability and safety of the embankment. These methods include replacing the original soil, stabilizing the soil using dolken piles and gradual mechanical compaction.The research results show that the success of berm construction is greatly influenced by thorough technical planning and coordination between work stages. This method has proven effective when applied to soft soil and provides constructive solutions to the technical problems that arise in the field.